Nutritional Factors Associated With Tonsillitis Among the School-going Children of District Mardan - Ullah, Said; Saeed, Usman; Rahman, Muhannad Iqbal Khan; Islam, Umair; Gul, Muhammad Kashif; Khan, Yaseen; Bibi, Maryam; Ali, Basit; Shahid, Ismail (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The aims of the study are to explore Nutritional factors associated with tonsillitis among the school-going children of aged 4 to 15 years in the local area of District Mardan. Institutional based cross-sectional study design was used. In the current research work a total of 500 samples were isolated from school-going children. In which 150 (30%) were found positive for nutritional deficiency with Tonsillitis. The samples collected from male and females students of age 4-15 years. Among the all samples nutritional anemia was found more frequent 60(12%), leading by malnutrition 50(10%), moderate prevalence were shows by underweight 20(4%) and stunting 16(3.2%) prevalence rate. while very low frequency was shows by wasting 4(1.6%) while the prevalence of tonsillitis was 45(9%) respectively. Out of 500 children the number of male was slightly higher than females. Nutritional Anemia and malnutrition were observed in the study in the school-going children respectively. The prevalence of nutritional Anemia among the study population varied with age. Children of the 12–15 years group had a significantly high prevalence of nutritional Anemia compared with the lower age group. It is concluded that all the nutritional factors strongly correlated with tonsillitis infection.